Nordnorsk Kunstmuseum - Campbell, Sandy (2024)
This building, designed in 1917 by Søren Andres Wiese Opsahl, was a post office and telegraph office, later a police station and since 1985 has housed the North Norwegian Art Museum. It contains more than 2,225 works from Troms, Finnmark, Nordland, Troms and Svalbard.